The role of diabetes knowledge and mediating effects of self-efficacy on diabetes knowledge toward diabetes self-care activities among Indonesian diabetes - Henik Tri Rahayu (Jurnal Keperawatan, 2022)
Introduction: Self-care activities is one of the critical element of controlling diabetes. Diabetes knowledge and self-efficacy were two main predictors suggested by evidence to be important in supporting diabetes self-care activities; both factors were also found to have a strong relationship. However, the minimal study explored the mediating effect of self-efficacy on diabetes knowledge toward diabetes self-care activities among Indonesian. Objectives: This study wants to explore the role of diabetes knowledge and examine the mediating effect of self-efficacy on diabetes knowledge toward diabetes self-care activities among Indonesian. Methods: This study was a cross-sectional-correlative study among 211 Indonesian adults with diabetes who utilized OPD Hospital in Malang, Indonesia. The primary valid and reliable instruments that measure diabetes knowledge, diabetes self-care activities, and self-efficacy were used in this study. Data were analyzed using SPSS 23 Software, and the mediating effect analysis examines using Hayes PROCESS software for SPSS. Results: Most subjects demonstrated low diabetes knowledge and self-efficacy and reported less than optimal self-care activities. Self-efficacy shows a 'complete mediating effect' in diabetes knowledge toward diabetes self-care activities. Conclusions: This study highlights the importance of diabetes knowledge and self-efficacy and both factors' existence in supporting diabetes self-care activities.